AN ANALYSIS OF PERSONALITY STRUCTURE ON MAIN CHARACTER AS SEEN IN BRAVE ANIMATION MOVIE BY BRENDA CHAPMAN : A PSICHOANALYSIS - Susel Piatun; Vera Magria; Dedi Efendi (Krinok:Jurnal Linguistik Budaya, 2022)
This study analyzes the structure of the human personality in an animated film entitled Brave by Brenda Chapman. The purposes of this study are 1) to explain the system of human personality structure in the main character of Brave movie, 2) to describe the impact that occurs on the dominance of the personality structure that appears in the main character of the film Brave. In conducting this study, the method used was a qualitative descriptive proposed by Endraswara (2013). The data was presented in the form of phrases, sentences and pictures related to the personality and characterization of the main character, the data analyzed based on the psychological theory by Sigmund Freud which groups 3 systems of human personality. Based on the results of the study, the writer found some data which was divided into three (3) forms of the main character's personality structure, namely Id, Ego and Super Ego. The writer found (16) sixteen data of personality structure , there were (7) seven Id structures, (4 ) four Ego structures and (5) five Super Ego structures. The data variation of acquisition was influenced by the shape of the character type on the main character. In addition, the writer also explains the impact of the dominance of the personality structure on  main character where the dominance of the Id has a negative impact while the Ego and Super Ego have a positive impact. The impact is formed based on the principles of each personality structure, namely the principles of pleasure, reality, and morals. From the data shown, in the main character, it can be conclude that the personality structure of Id was found more. Namely the urge to act as desired with the aim of relieving a pressure in the main character. there was a change in the negative impact to be positive at the end of the story, this caused by the round type of character in the main character which affects the change in the attitude of the main character in the story of the Brave movie.